The endearment - Spencer, LaVyrle (New York : Jove, 1990)
Fiery-tempered beauty Anna Reardon had only one chance to escape the shameful street-urchin's life forever--to become Karl Lindstrom's mail-order bride. Karl soon discovered Anna's true background, but there was one burning secret that Anna will never be able to reveal. . . .
A novel.
Keywords: Love stories